Evaluation of the Website Quality of a Faculty of Animal Science Using WebQual 4.0 and Importance Performance Map Analysis - Mangara Sitinjak; Josua Josen A Limbong; Julius Putra P Naibaho (LPPM Universitas Bhinneka Nusantara, 2026)
The present study seeks to assess the quality of the Faculty of Animal Science website at the University of Papua and determine key areas requiring improvement based on user perceptions using the WebQual 4.0 method, PLS-SEM, and IPMA. Data were collected through an online questionnaire involving 110 respondents consisting of students, lecturers, and educational staff. The findings indicated that all indicators satisfied the standards for both validity and reliability, confirming their suitability for further analysis. The evaluation of the structural model indicated that user satisfaction was significantly and positively influenced by only usability (β = 0.343; t = 2.962; p = 0.003), while no significant effects were identified for information quality and service interaction quality. The Q²predict value of 0.229 suggests that the model has acceptable predictive relevance, while the coefficient of determination (R² = 0.293) indicates that the model demonstrates weak to moderate explanatory power. Furthermore, usability demonstrated the largest practical contribution to user satisfaction with an f² value of 0.091, although the effect size remained within the small category. IPMA results at the construct level identified usability as the highest priority for improvement, with an importance score of 0.343 and a performance score of 59.437. At the indicator level, indicator related to ease of use and navigation, particularly indicators U1 and U3, were identified as the primary areas requiring improvement. Meanwhile, service interaction quality demonstrated relatively high performance and should be maintained, whereas information quality requires gradual enhancement. Therefore, efforts to improve website quality should prioritize usability while continuously improving information quality and service interaction quality to enhance user satisfaction.